2018
DOI: 10.1002/ajp.22739
|View full text |Cite
|
Sign up to set email alerts
|

Rhesus macaque personality, dominance, behavior, and health

Abstract: Previous studies of nonhuman primates have found relationships between health and individual differences in personality, behavior, and social status. However, despite knowing these factors are intercorrelated, many studies focus only on a single measure, for example, rank. Consequently, it is difficult to determine the degree to which these individual differences are independently associated with health. The present study sought to untangle the associations between health and these individual differences in rh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
28
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(33 citation statements)
references
References 40 publications
1
28
2
Order By: Relevance
“…It has been suggested that high levels of sociality are usually associated with good animal health (Capitanio, 2011; Jin et al, 2013; Robinson et al, 2018). Social grooming, for instance, is important for removal of ectoparasites, maintenance of social bonds, and/or to reduce social tension in groups of nonhuman primates (Dunbar, 1991; Lehmann, Korstjens, & Dunbar, 2007).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been suggested that high levels of sociality are usually associated with good animal health (Capitanio, 2011; Jin et al, 2013; Robinson et al, 2018). Social grooming, for instance, is important for removal of ectoparasites, maintenance of social bonds, and/or to reduce social tension in groups of nonhuman primates (Dunbar, 1991; Lehmann, Korstjens, & Dunbar, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Individual differences in sociality can influence the general health of animals, including primates (Capitanio, 2011). Nonhuman primates involved in more social interactions have more health benefits than less social individuals (baboons, Papio cynoceph alus , Silk, Alberts, & Altmann, 2003; golden snub‐nosed monkeys, Rhinopithecus roxellana , Jin, Su, Tao, Guo, & Yu, 2013; rhesus macaques, Macaca mulatta , Robinson et al, 2018). However, social interactions may also negatively influence health (Rushmore, Bisanzio, & Gillespie, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Yet, so far, not many animal personality studies have involved common behaviour coding in personality model assessment (some exceptions include Anestis, 2005;Freeman et al, 2013;Garai et al, 2016;Iwanicki and Lehmann, 2015;Konečná et al, 2008;Neumann et al, 2013;Pederson et al, 2005;Robinson et al, 2018;Sussman et al, 2014Sussman et al, , 2013.…”
Section: Introductionmentioning
confidence: 99%
“…Consistent personality ratings have been identified for several nonhuman animal species and interest and knowledge of primate personality in particular has been expanding over the past couple of decades (Freeman & Gosling, ; Weiss, ). Studying macaque personality is important because this genus is commonly housed in captivity and understanding more about their individual differences might enhance our understanding of how to provide the best possible care for them (Capitanio, ; Coleman, ; Robinson et al, ; Rouff, Sussman, & Strube, ).…”
Section: Introductionmentioning
confidence: 99%